Deschooling Concept in Islamic Education: a Comparative Study of Ivan Illich and Ki Hajar Dewantara - Riyazati, Shushmittha; Muhid, Abdul (MUADDIB Jurnal Kependidikan dan Keislaman, 2024)
This research analyzes and compares Ivan Illich's concept of "deschooling" and Ki Hajar Dewantara's educational thought, exploring their implications for the development of Indonesia's education system. Both Illich, a Mexican thinker, and Dewantara, a national figure in Indonesia, have critiqued the limitations of formal education. Illich advocates for the radical elimination of the formal school system through "deschooling," while Dewantara proposes a more integrated approach with the Tri Center of Education and the Among System, emphasizing the collaboration of family, community, and school. Using a qualitative approach and literature review, the research examines the background, principles, and implications of these two thinkers' educational concepts. Theories of critical education and humanism provide the theoretical framework for analyzing their ideas. The findings highlight both shared critiques of formal education’s failure to meet societal needs and differences in their proposed solutions. While Illich calls for a fundamental shift away from schools, Dewantara aims to create a more inclusive and human-centered educational system. Despite their contrasting approaches, both thinkers share a commitment to empowering individuals and communities in the learning process, offering valuable insights for reforming education in Indonesia.